Sensitivity Towards Sociocultural Plagiarism in the Context of Varied Discipline among College Students - Lillian C. Calicdan; Rhyan Mike R. Bacaro; Dennis C. Ramo; Rodrigo Jr Licayan (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
Socio-cultural plagiarism provides an understanding of the social values and attitudes among students in academic writing. Based on the rules and regulations of any academic institution, adequate awareness of different forms of plagiarism, citation techniques, paraphrasing, and other instances of copyright infringement should be tailored to any type of violation against conduct and discipline, particularly in cheating. A descriptive-comparative approach uses this study to measure the level of sensitivity among students towards socio-cultural plagiarism in terms of awareness, attitude, socio-cultural beliefs, and perception. Applying Slovin's formula, the respondents were identified using a simple random sampling technique. The results revealed that the level of sensitivity among students towards socio-cultural plagiarism is low. It is also revealed that there is no significant difference in the level of sensitivity among students towards socio-cultural plagiarism when respondents are grouped according to discipline. Therefore, as the basis for an intervention program, ethical standards of writing and the tools or technology to detect plagiarized output of the students are crucial elements towards the institution's academic standards.